A randomized controlled trial evaluating the effects of a family-centered HIV care model on viral suppression and retention in care of HIV-positive children in Eswatini. - Kim Ashburn (Public Library of Science (PLoS), 2021)
Introduction A family-centered care model (FCCM) providing family-based HIV services, rather than separate adult/pediatric services, has been proposed to increase pediatric retention and treatment adherence. Materials and methods Eight health-care facilities in the Hhohho region of Eswatini were randomized to implement FCCM (n = 4) or continue standard-of-care (SOC) separate adult/pediatric clinics (n = 4). HIV-positive children and caregivers were enrolled; caregiver interview and child/caregiver chart abstraction were done at enrollment and every three months; pediatric viral load was evaluated at enrollment and every six months through 12 months. Because of study group differences in 12-month viral load data availability (89.4% FCCM and 72.0% SOC children had 12-month viral load), we used three separate analyses to evaluate the effects of FCCM on children's viral suppression (<1,000 copies/mL) and undetectable virus (<400 copies/mL) at 12 months. In the first analysis, all children with missing viral outcome data were excluded from the analysis (modified intent to treat, mITT). The second analysis used inverse probability of missingness weighted logistic regression to estimate the effect of FCCM on 12-month viral outcomes compared to SOC (weighted mITT). For the third approach, missing virologic outcome data were imputed as virologic failure (imputed ITT). We also examined factors associated with viral suppression at 12 months using multivariable logistic regression. Results We enrolled 379 HIV-positive children and 363 caregivers. Among all children at enrollment, viral suppression and undetectability was 78.4% and 73.9%, respectively, improving to 90.2% and 87.3% at 12 months. In mITT and weighted mITT analyses, there was no significant difference in children's 12-month viral suppression between FCCM and SOC groups (89.2% and 91.6%, respectively). Using imputed ITT, there was a modest increase in 12-month viral suppression in FCCM versus SOC children (79.7% and 69.8%, respectively, p = 0.051) and 12-month undetectability (78.7% and 65.7%, respectively, p = 0.015). Among the 255 children suppressed at enrollment, more FCCM versus SOC children (98.0% versus 95.3%) were suppressed at 12-months, but this was not statistically significant in mITT or weighted mITT analyses, with a marginally significant difference using imputed mITT analysis (p = 0.042). A higher proportion of children suppressed at enrollment had undetectable viral load at 12 months in FCCM versus SOC children (98.0% versus 92.5%), a statistically significant difference across analytical methods. Among the 61 children unsuppressed at enrollment, achieving suppression was higher among SOC versus FCCM children, but this difference was not statistically significant and included only 38 children; and there were no significant differences in detectable viral load at 12 months. There were no significant differences between study groups in retention or ART adherence at 12 months for children or caregivers. Factors associated with lack of viral suppression/detectability at 12 months included lack of viral suppression at enrollment and having a younger caregiver (age <25 years). Conclusions FCCM in Eswatini was associated with a modest increase in viral suppression/undetectability at 12-months; 12-month retention and adherence did not differ by study group for children or caregivers. High levels of suppression and retention in both groups may have limited our ability to detect a difference. Trial registration NCT03397420; ClinicalTrials.gov.